2014
DOI: 10.1089/jir.2013.0097
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Interferon Beta Antibody Titers Strongly Correlate Between Two Bioassays and In Vivo Biomarker Expression, and Indicates That a Titer of 150 TRU/mL Is a Biologically Functional Cut-Point

Abstract: Interferon beta (IFNβ) is used as a first-line treatment in relapsing-remitting multiple sclerosis (MS). The occurrence of neutralizing antidrug antibodies (NAbs) against IFNβ may reduce treatment response. Therefore, clinical monitoring of NAbs is currently executed using bioassays, but several bioassays are available and it is unclear how well their readouts correlate. We made a comparison between 2 bioassays; myxovirus resistance protein A (MxA) gene expression assay (MGA) and iLite™ anti-Human IFNβ bioassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(2 reference statements)
1
10
0
Order By: Relevance
“…The ADA assay methods which have changed across time in Sweden and Austria were associated with ADA occurrence, suggesting a difference in the sensitivity of the assays as previously reported [18]. The MPA method detected a higher rate of ADA with 20% (95% CI 14.7–25.1) of the patients who developed ADA before 18 months of therapy in Austria and 30.3% (95% CI 18.6–36.1) in Sweden, while 7% (95% CI 1.3–10.7) developed ADA with the MGA method in Austria and 8.4% (95% CI 6.9–10.6) in Sweden.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The ADA assay methods which have changed across time in Sweden and Austria were associated with ADA occurrence, suggesting a difference in the sensitivity of the assays as previously reported [18]. The MPA method detected a higher rate of ADA with 20% (95% CI 14.7–25.1) of the patients who developed ADA before 18 months of therapy in Austria and 30.3% (95% CI 18.6–36.1) in Sweden, while 7% (95% CI 1.3–10.7) developed ADA with the MGA method in Austria and 8.4% (95% CI 6.9–10.6) in Sweden.…”
Section: Resultsmentioning
confidence: 82%
“…We cannot assess the effect of change in IFNβ-1a s.c. formulation as its date is too close to the date of change in type of assay used. Nevertheless when we adjusted on the type of IFNβ treatment in the multivariate analyses, differences between the assay methods in terms of ADA development remained significant, suggesting that assay methods may differ in sensitivity of ADA detection as previously reported [18]. …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is the high‐titre nADA that are responsible for the blocking of the biological effect of IFN‐ β . This blocking is titre dependent, and the biological threshold can be determined by pharmacodynamic studies correlating the intended gene expression stimulation of the drug with levels of nADA . Neutralizing ADA are measured in bioassays in which the stimulation of the cells with IFN‐ β is blocked by the addition of patients' serum and thus mimicking the biological significance of nADA.…”
Section: Ada In Ms Patients Treated With Ifn‐βmentioning
confidence: 99%
“…Each laboratory should establish its own threshold. Using two different assays for NAbs quantification Hermanrud and collaborators [37] found that a titer over 150 was associated with loss of IFNβ biological activity.…”
Section: High Titer Of Nabs Abolishes the Biological Activity Of Ifnβmentioning
confidence: 99%